2019
DOI: 10.3390/ijerph16245102
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Pollution: Health and Economic Effect Assessment Based on a Recursive Dynamic Computable General Equilibrium Model

Abstract: At present particulate matter (PM 2.5 ) pollution represents a serious threat to the public health and the national economic system in China. This paper optimizes the whitening coefficient in a grey Markov model by a genetic algorithm, predicts the concentration of fine particulate matter (PM 2.5 ), and then quantifies the health effects of PM 2.5 pollution by utilizing the predicted concentration, computable general equilibrium (CGE), and a carefully designed exposure-response model. Further, the authors esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In China, there are 156,588 premature deaths and more than 6 million individuals suffer from air pollution-related diseases annually. This has caused a loss of 3,026.62 million Chinese yuan in labor losses and medical expenditure (Chen et al, 2019). For the United States, Deryugina et al (2019) reported that an increase in PM2.5 of 1 microgram per cubic foot led to a loss of 2.99 life years per 1 million beneficiaries over three days, amounting to a loss of 299,000 dollars.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there are 156,588 premature deaths and more than 6 million individuals suffer from air pollution-related diseases annually. This has caused a loss of 3,026.62 million Chinese yuan in labor losses and medical expenditure (Chen et al, 2019). For the United States, Deryugina et al (2019) reported that an increase in PM2.5 of 1 microgram per cubic foot led to a loss of 2.99 life years per 1 million beneficiaries over three days, amounting to a loss of 299,000 dollars.…”
Section: Introductionmentioning
confidence: 99%